Kepemimpinan Tranformasional, Kepercayaan dan Berbagi Pengetahuan dalam Organisasi - Kardenal, Kardenal (Sekolah Tinggi Ilmu Pemerintahan Abdi Negara, 2017)
Many research in knowledge sharing has focused their attention on the roles of information and technology factor. Recently, there is a consideration that human factors such as social interaction, trust and leadership play keyroles in knowledge sharing behavior. This study aimed to investigate the factors affecting emplyees knowledge sharing within an organization by combining transformational leadership and trust as predictor of knowledge sharing behavior. This research used survey ethod, and take 99 employees of PT. Bina Karya Jakarta as sample. The instruments to get data was quistionnaire of Likert's Scale, that consisted of leadership scale, organizaional trust scale, managerial trust, co-worker trust scale and knowledge sharing scale. The research found that transformational leadership, organizaional trust, management trust and co-worker trust together have significant effect on knowledge sharing behavior with r=0,264. The regression coefficient also shows there is only the co-worker trust that have the most significant effect on knowledge sharing behavior. These findings ned to be discussed for futher research especially to gain understanding about the role trasformational leadership and trust on knowledge sharing that vary, depends on the situation and condition.